Optically switched magnetism in photovoltaic perovskite CH3NH3(Mn:Pb)I3 - B. Náfrádi (Nature Portfolio, 2016)
Functional behaviour can emerge in materials in which magnetic order is determined by the interplay of localised and itinerant magnetic interactions. Here the authors tune such magnetic order in a photovoltaic perovskite by tuning the electronic carrier concentration under visible light illumination.